Study of Medico-legal cases in a Tertiary Care Teaching Hospital (Medico Legal Update, 2024)
Medico-legal cases are pivotal in the pursuit of justice for victims and the accused. It is essential for medical professionals to be well-versed in the intricacies of medico-legal cases to ensure that they follow the procedures of the law of the land diligently. Understanding the patterns of medico-legal cases in a specific region can assist government authorities in devising strategies to prevent such incidents. This study was conducted at a rural tertiary care teaching hospital over a span of seven months, from January to July 2023, and examined 139 medicolegal cases. The age group of 21 to 40 years, predominantly comprising males, emerged as the most affected demographic in our study. Road traffic accidents were the predominant cause of medico-legal cases, with head injuries being the most frequently observed. Understanding the demographics and injury patterns of medico-legal cases in this rural area serves as a foundation for tailoring medical care and legal interventions to the specific needs of the community. By continuing to investigate and analyze medico-legal cases, healthcare providers and law enforcement agencies can work collaboratively to not only address the immediate medical needs of victims but also to develop proactive strategies to minimize the occurrence of such cases and improve overall community well-being.